Comparative genomics reveals insights into characterization and distribution of quorum sensing-related genes in Shewanella algae from marine environment and clinical sources. (December 2020) - Chen, Ying-Ju; He, Guo-Cheng; Cheng, Jan-Fang; Lee, Yi-Tzu; Hung, Yu-Hsuan; Chen, Wen-Huei; Huang, Yao-Ting; Liu, Po-Yu
Highlights: Whole genome sequence of S. algae to investigate the core genetic elements and QS-related genes. The LuxR solos systems exist in S . algae . luxS gene in S. algae is phylogenetically conserved. Abstract: Shewanella algae is not only the most commonly reported species in Shewanella human infections but also capable to inhabit a wide variety of habitats. Although there is evidence that quorum sensing is associated with bacterial adaptation to changing environmental conditions, little is known of the quorum sensing system in S . algae . In this study, we conducted the whole genome sequencing of S . algae strains and applied comparative genomics to reveal the core genome. Genes related to the quorum sensing system were identified by integrated bioinformatics analysis. S . algae harbor genes involved in all three main types of autoinducer systems. This study provides insights into the quorum sensing systems in S . algae, which might be valuable in the future study of cell behavior in S . algae .